The effect of read-aloud assistance on the text comprehension of dyslexic and non-dyslexic English language learners. (January 2019) - Košak-Babuder, Milena; Kormos, Judit; Ratajczak, Michael; Pižorn, Karmen
One of the special arrangements in testing contexts is to allow dyslexic students to listen to the text while they read. In our study, we investigated the effect of read-aloud assistance on young English learners' language comprehension scores. We also examined whether students with dyslexia identification benefit from this assistance differently from their peers with no official identification of dyslexia. Our research was conducted with young Slovenian learners of English who performed four language assessment tasks adapted from a standardized battery of Slovenian national English language tests. In a counter-balanced design, 233 students with no identified dyslexia and 47 students with dyslexia identification completed two language comprehension tasks in a reading-only condition, one task with read-aloud assistance and one task in listening-only mode. We used Generalized Linear Mixed-Effects Modelling (GLMM) to estimate accurately the effects of the mode of administration, dyslexia status, and input text difficulty, while accounting for error variance owing to random differences between students, texts, and questions. The results of our study revealed that young L2 learners with no dyslexia identification performed similarly in the three conditions. The read-aloud assistance, however, was found to increase the comprehension scores of dyslexic participants when reading difficult texts, allowing them to perform at the level of their non-dyslexic peers. Therefore, our study suggests that this modification of the test administration mode might assist dyslexic students in demonstrating their text comprehension abilities.